Penyesuaian Diri Dan Komunikasi Interpersonal Pendatang Baru Sebagai Ide Penciptaan Seni Lukis Digital - Saraswati, Intan; Utami, Ni Made Purnami; Pemayun, Tjokorda Udiana Nindhia (Program Studi Seni Murni ISI Bali, 2024)
The purpose of this writing is to describe the visualization process which includes: concepts, themes, techniques and forms of painting works with the title Self-Adjustment and Interpersonal Communication for Newcomers as Ideas for Creating Digital Painting Art. The methods used in creating digital painting works of art are exploration, experimentation and execution. Exploration in creating digital works of art includes research, theme exploration and model exploration, namely combining themes and concepts and determining the poses of female figures by means of observation. The experimental method was carried out to discover new things such as the use of effects in the Adobe Photoshop application and to apply ideas and notions to the creation of digital works of art by applying filters to the photo images that will be used, then continuing with experiments on combining the drawn figures. with photo images that have been edited in the Adobe Photoshop application. The execution stage is carried out by moving the sketch to a new layer. After the discussion and creative process, it can be concluded: 1.) The concept in creating digital painting works of art is to express thoughts and feelings into digital works of art by using female figures as the main objects as symbols of feelings that have meaning regarding each event that occurs. experienced by the author related to the phenomenon of adapting to a new environment and visualized with a surrealistic approach. 2.) The concept in creating digital painting works of art is to express experiences or phenomena related to interpersonal communication and self-adjustment experienced by artists in their lives. 3.) The manufacturing technique uses the Adobe Photoshop application and the IbisPaint digital drawing application and later combines photo images and figure drawings drawn manually. 4.) The form in the painting visualization displays a self-portrait painting with a surrealistic style and is inspired by the Art Nouveau art style which depicts female figures and other objects as symbols arranged by adjusting the composition so that it looks harmonious.